Diagnóstico de los recursos humanos para la mejora del funcionamiento de los establecimientos de hospedaje en la ciudad de Manta. - Zambrano Zambrano, Jennifer Nathalie (2018)
This research is descriptive and its purpose is to diagnose human resources in lodging establishments in the city of Manta. As part of the research process, several methodologies were consulted to guide and structure one's own that can integrate all the necessary elements for the development of this work. From this, six stages were considered; the first focused on the selection of hotel hotels establishments of the fourth and fifth category. In the second stage the respective characterization was developed to understand how the hotels under study are organized, determine their services, facilities and markets. The third stage was the preparation for the diagnosis, in which seven professionals who work in the area of human talent were selected, they formed the work team for the application of information gathering tools and in turn the schedules of visits to the respective establishments. The fourth stage is the development of the human resources diagnosis and focused on the execution of an internal, external analysis, execution of the DAFO matrix, analysis of the work environment and management of human talent, which was possible through the application of interviews and surveys. The results obtained from the diagnosis allowed five improvement actions to be formulated, such as: criteria for the correspondence of the labor position, training program, internal communication manual, internal audit indicators and considerations for the identification of incentives, and as a sixth stage, the evaluation and follow-up of the proposals was proposed.